Аналіз методів енергоефективності в технології мобільного зв’язку 5G - Мазепа, К. М.; Хвостик, І. О.; Аль-Вандаві Саіф Ахмед Іскандар Ісмаель (ХНУРЕ, 2021)
The analysis of energy efficient methods used in the technology of the new 5G standard is carried out. It is hypothesized that it is expedient to implement energy efficiency methods in 5G by introducing them into the connection control plane, which will allow to take into account the state of the network for machine learning analysis when processing information [10-11].
Keywords: Аналіз методів енергоефективності; Технології мобільного зв'язку 5G